All out - Mitchell, Saundra; McLemore, Anna-Marie; Parker, Natalie C.; Magruder, Nilah; Lee, Mackenzi; Talley, Robin; Lo, Malinda; Adler, Dahlia; Scelsa, Kate; Wake, Elliot; Tracey, Scott, 1979-; Sharpe, Tess; et al. (Inkyard Press, 2020)
Take a journey through time and genres and discover a past where queer figures live, love and shape the world around them. Seventeen of the best young adult authors across the queer spectrum have come together to create a collection of beautifully written diverse historical fiction for teens. From a retelling of Little Red Riding Hood set in war-torn 1870s Mexico featuring a transgender soldier, to an asexual girl discovering her identity amid the 1970s roller-disco scene, this collection of short stories crosses cultures and time periods to shed light on an area of history often ignored or forgotten.